Pesantren Counseling Through Al-Irshad wa Al-Taujih Services - Heri Fadli Wahyudi; Ummul Maghfiroh (Al-Ihath: Jurnal Bimbingan dan Konseling Islam, 2023)
In the process of living disciplined in TMI Islamic boarding schools, some problems occur naturally in every student. One of the programs in guidance and counseling at TMI Al-Amien Prenduan is called al-Irsyad wa al-Taujih, which is intended to help students carry out daily discipline both periodically and when they get into difficulties. The problem raised in this study is how the service of al-Irshad wa al-Taujih at TMI Al-Amien Prenduan is in the perspective of pesantren counseling. To find out more about the benefits of al-Irshad wa al-Taujih, researchers use qualitative descriptive research methods, with sources of an interview, observation, and documentation data. Data analysis uses Miles and Huberman's theory by reducing data, presenting data, and drawing conclusions. As for the validity of the data, researchers used cross-triangulation between informants and cross-triangulation between methods. From the results of the research conducted, it can be concluded as follows: 1. Guidance and counseling services provided to all Santriwati with the Halaqoh (discussion), Uswatun Hasanah (good example), and Maw'izah Hasanah (good advice) methods to revitalize and direct Santriwati in every problem. The ministry of al-Irshad wa al-Taujih is carried out both in the classroom and outside the school, assisted by Mulahidhah, Ustadzah, Musyrifah, Mutsakkifah, and mudir Ma'had. 2. The impact of al-irsyad wa al-taujih's service at TMI Putri Al-Amien Prenduan positively impacts all TMI students; the students feel more motivated and understand more about the problems they are experiencing.